Endoscopic ultrasound guided fine‐needle aspiration vs core needle biopsy for solid pancreatic lesions: Comparison of diagnostic accuracy and procedural efficiency. Issue 11 (16th July 2019) - Syed, Aslam; Babich, Olivia; Rao, Bharat; Singh, Shailendra; Carleton, Neil; Gulati, Abhishek; Kulkarni, Archana; Garg, Mrinal; Farah, Katie; Kochhar, Gursimran; Morrissey, Suzanne; Mitre, Marcia; et al.
Abstract: Background: Endoscopic ultrasound (EUS) guided core needle biopsies (CNB) are increasingly being performed to diagnose solid pancreatic lesions. However, studies have been conflicting in terms of CNB improving diagnostic accuracy and procedural efficiency vs fine‐needle aspiration (FNA), which this study aims to elucidate. Methods: Data were prospectively collected on consecutive patients with solid pancreatic or peripancreatic lesions at a single tertiary care center from November 2015 to November 2016 that underwent either FNA or CNB. Patient demographics, characteristics of lesions, diagnostic accuracy, final and follow‐up pathology, use of rapid on‐site evaluation (ROSE), complications, and procedure variables were obtained. Results: A total of 75 FNA and 48 CNB were performed; of these, 13 patients had both. Mean passes were lower with CNB compared to FNA (2.4 vs 2.9, P = .02). Use of ROSE was higher for FNA (97.3% vs 68.1%, P = .001). Mean procedure time was shorter with CNB (34.1 minutes vs 51.2 minutes, P = .02) and diagnostic accuracy was similar (89.2% vs 89.4%, P = .98). There was no difference in diagnostic accuracy when ROSE was performed for CNB vs not performed (93.5% vs 85.7%, P = .58). Additionally, diagnostic accuracy of combined FNA and CNB procedures was 92.3%, which was comparable to FNA ( P = .73) or CNB ( P = .52) alone. Conclusion: FNA and CNB had comparable safety and diagnostic accuracy. Use of CNB resulted in less number of passes and shorter procedure time as compared to FNA. Moreover, diagnostic accuracy for CNB with or without ROSE was similar.